Long-term neurocognitive dysfunction in sports: What Is the evidence? - Solomon, G. S.; Ott, S. D.; Lovell, M. R. (Clinics in Sports Medicine, 2011)
Although the immediate neurocognitive effects of sports-related concussion are well known, less is known about the intermediate or long-term effects of sports-related concussions. A sample of selected studies of high-school and collegiate athletes is reviewed and the intermediate effects of concussive injuries are discussed, because no long-term empiric data are available with these populations. The evidence for intermediate neurocognitive effects is mixed and not convincing at present in these groups of athletes. Selected studies of professional boxers and American professional football players are also reviewed, and the available data regarding long-term neurocognitive and neuropathologic effects are assessed. The evidence for long-term adverse neurocognitive effects in professional boxers is compelling. Suggestions for future research on relevant biopsychosocial variables affecting response to concussive injury are presented.